How does decentralisation affect health sector planning and financial management? a case study of early effects of devolution in Kilifi County, Kenya - Benjamin Tsofa; Sassy Molyneux; Lucy Gilson; Catherine Goodman (BMC, 2017)
Abstract Background A common challenge for health sector planning and budgeting has been the misalignment between policies, technical planning and budgetary allocation; and inadequate community involvement in priority setting. Health system decentralisation has often been promoted to address health sector planning and budgeting challenges through promoting community participation, accountability, and technical efficiency in resource management. In 2010, Kenya passed a new constitution that introduced 47 semi-autonomous devolved county governments, and a substantial transfer of responsibility for healthcare from the central government to these counties. Methods This study analysed the effects of this major political decentralization on health sector planning, budgeting and overall financial management at county level. We used a qualitative, case study design focusing on Kilifi County, and were guided by a conceptual framework which drew on decentralisation and policy analysis theories. Qualitative data were collected through document reviews, key informant interviews, and participant and non-participant observations conducted over an eighteen months' period. Results We found that the implementation of devolution created an opportunity for local level prioritisation and community involvement in health sector planning and budgeting hence increasing opportunities for equity in local level resource allocation. However, this opportunity was not harnessed due to accelerated transfer of functions to counties before county level capacity had been established to undertake the decentralised functions. We also observed some indication of re-centralisation of financial management from health facility to county level. Conclusion We conclude by arguing that, to enhance the benefits of decentralised health systems, resource allocation, priority setting and financial management functions between central and decentralised units are guided by considerations around decision space, organisational structure and capacity, and accountability. In acknowledging the political nature of decentralisation polices, we recommend that health sector policy actors develop a broad understanding of the countries' political context when designing and implementing technical strategies for health sector decentralisation.